2013
DOI: 10.1002/pssc.201200640
|View full text |Cite
|
Sign up to set email alerts
|

CHVPE growth of AlGaN‐based UV LEDs

Abstract: In this paper, we present results on development of ultraviolet light‐emitting diodes (UV LEDs) based on GaN/AlGaN heterostructures grown on Al2O3 (0001) substrates by chloride‐hydride vapour phase epitaxy (CHVPE). Both packaged and unpackaged UV LED dies were fabricated. The peak wavelengths of dies were in the range of 360–365 nm with a typical FWHM of 10–13 nm. UV LEDs proved performance capability at current density up to 125 A/cm2. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Since dislocations are known to be the main centers contributing to nonradiative recombination this in turn makes it possible to switch from MQW active region to a relatively thick double heterostructure (DH) region design, which decreases the effective carrier injection density and relieves the problems caused by Auger recombination . Some of the authors of the present paper have shown that efficient NUV (wavelength 350–360 nm) DH AlGaN/GaN LEDs can be fabricated by HVPE on sapphire . However, the external quantum efficiency of these LEDs at the moment falls seriously behind the efficiency of MQW NUV LEDs prepared by MOCVD .…”
Section: Introductionmentioning
confidence: 99%
“…Since dislocations are known to be the main centers contributing to nonradiative recombination this in turn makes it possible to switch from MQW active region to a relatively thick double heterostructure (DH) region design, which decreases the effective carrier injection density and relieves the problems caused by Auger recombination . Some of the authors of the present paper have shown that efficient NUV (wavelength 350–360 nm) DH AlGaN/GaN LEDs can be fabricated by HVPE on sapphire . However, the external quantum efficiency of these LEDs at the moment falls seriously behind the efficiency of MQW NUV LEDs prepared by MOCVD .…”
Section: Introductionmentioning
confidence: 99%
“…Hydride vapor phase epitaxy (HVPE) is a well-known method for fabrication thick low-defect quasi-bulk or freestanding GaN materials and GaN-based templates to serve as substrates for device structures growth by other techniques such as MBE and MOCVD. It was also demonstrated that HVPE can be successfully used to grow the whole device structures for application in visible and UV LEDs and power electronics [1][2][3][4].…”
mentioning
confidence: 99%
“…We have reported on AlGaN-based LED heterostructures emitting at 350-360 nm [4]. In this paper we report on growth of UV LED heterostructures by HVPE on sapphire substrates and results of the heterostructures characterization by high-resolution X-ray diffractometry 2 Sample and experimental technique The Al-GaN-based UV LED heterostructures up to 11 μm thick were grown on c-plane 2-inch sapphire substrates in a conventional horizontal-flow reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All this makes HVPE a very promising technique for fabrication of bulk GaN that can be used as substrates in nitrides epitaxy. HVPE GaN films and device structures can be also very useful for light emitting diodes, high-power rectifiers, transistors and radiation detectors (Dmitriev and Usikov, 2006;Reed et al, 2009;Kurin et al, 2013;Wang et al, 2011;Pearton et al, 2013) however, present day HVPE films still suffer from a rather high residual donor concentration (typically undoped GaN films are n-type with the uncompensated shallow donor density of ~10 17 cm −3 or even higher) and relatively high density of deep electron and, particularly, hole traps (Lee et al, 2012;Polyakov et al, 2011;Fujito et al, 2009;Yoshida et al, 2008), which seriously limits their applications in device structures. In what follows we analyze how the growth conditions (growth temperature especially) affect the electrical and optical properties and the deep traps spectra of HVPE layers.…”
Section: Introductionmentioning
confidence: 99%